The Influence of Electronic Word of Mouth and Brand Image on Purchase Intention in Tuku Coffee Shops the Tangerang Area - Andi Hidayat Muhmin; Shakila Puja Meisye (Formosa Journal of Sustainable Research, 2023)
The use of digital media such as social media is used by coffee shop businessmen in introducing and promoting coffee brands and products so that they can attract the interest of consumers who see them. This study aims to determine the effect of Electronic Word of Mouth and Brand Image on Buying Interests of Tuku Coffee Shops in the South Tangerang area, using a total sample of 100 respondents to consumers who have bought and consumed Tuku Coffee in the last 2 months. The method used in this study is the Multiple Linear Regression Analysis technique. In this study using a type of quantitative research using a Likert scale with the Non Probability Sampling method through the Purposive Sampling technique.  The results of this study indicate that Electronic Word of Mouth (E-WOM) and Brand Image have a positive and significant effect on Purchase Intention. Then the Electronic Word  of  Mouth   (E-WOM)   and  Brand   Image simultaneously influence the Buying Interest of Toko Kopi Tuku products. Thus      increasing Electronic Word of Mouth (E-WOM) will increase Buying Interest  in  products  and  a  good  Brand Image will increase Buying Interest in consumers of Tuku Coffee Shop